EFEKTIFITAS LUMBO SACRO ORTHOSIS (LSO) SEBAGAI KURATIF PADA PASIEN NYERI PUNGGUNG BAWAH - Alfan Zubaidi; Muh. Syaiful Akbar; Dody Suprayogi; Amaliah Amriani (J-KESMAS: Jurnal Kesehatan Masyarakat, 2025)
Lower back pain (LBP) is one of the leading causes of disability worldwide and a major public health issue that affects productivity and quality of life. This study aimed to evaluate the curative effectiveness of Lumbo Sacro Orthosis (LSO) in reducing pain intensity among patients with LBP in Karanganyar Regency, Central Java. Using a pretest–posttest one-group design, 50 respondents aged 25-60 years who experienced nonspecific LBP with a Visual Analog Scale (VAS) score ≥3 were recruited using purposive sampling. The intervention involved daily use of LSO for two weeks, with pain intensity measured before and after treatment using the VAS instrument. Data were analyzed using the Wilcoxon Signed-Rank Test and paired sample t-test, depending on data distribution. The results revealed a significant reduction in mean VAS score from 4.30 ± 0.61 (moderate pain) to 2.26 ± 0.78 (mild pain), with a mean difference of 2.04 and p < 0.05, indicating strong statistical significance. The effect size (Cohen’s d = 2.76) suggested a very large clinical effect. These findings demonstrate that LSO effectively reduces LBP intensity and enhances patient comfort and mobility. From a public health perspective, the application of LSO within community-based physiotherapy services can serve as a practical and accessible curative strategy to alleviate musculoskeletal pain, enhance functional capacity, and improve quality of life among working-age populations.